Physiological and biochemical measurements on Pycnogonida from McMurdo Sound - Moran, Amy; Tobalske, Bret; Woods, H. Arthur (IEDA: US Antarctic Program Data Center, 2018)
Abstract: This dataset contains morphometric (mass, surface area, cuticle thickness, cuticle morphometrics) and physiological (oxygen consumption) data for Antarctic pycnognonids collected in McMurdo Sound, Antarctica .